1996
DOI: 10.1099/00222615-45-2-127
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the clonal variants of Serratia marcescens that infect the eye during contact lens wear

Abstract: Serratia marcescens colonises contact lenses during wear, although the frequency of isolation is generally low (0.6% contamination rate). A method for typing the S. marcescens colonising the eye or contact lens was developed, based upon ribotyping, serotyping and biotyping. Twelve different types of S. marcescens were isolated from the eyes, contact lenses, contact lens cases and fingers of contact lens wearers in the Sydney area over a 2-year period. There was no evidence of a specific type being more readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Moreover, this organism is a good colonizer of living and inanimate surfaces. For example, S. marcescens strains can consistently be isolated from contact lenses and contact lens cases (19,31), and S. marcescens MG1 has previously been shown to colonize tomato roots (60). In light of this general control, we studied QS regulation of attachment and found that QS mediates attachment to some surfaces, such as hydrophilic, polystyrene microtiter plates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this organism is a good colonizer of living and inanimate surfaces. For example, S. marcescens strains can consistently be isolated from contact lenses and contact lens cases (19,31), and S. marcescens MG1 has previously been shown to colonize tomato roots (60). In light of this general control, we studied QS regulation of attachment and found that QS mediates attachment to some surfaces, such as hydrophilic, polystyrene microtiter plates.…”
Section: Discussionmentioning
confidence: 99%
“…Serratia marcescens has been implicated in both CLARE and corneal ulceration, but may also colonize the eye in low numbers without any overt pathogenic symptoms (5). This study has shown that there are differences between isolates of S. marcescens in their ability to evade complement attack, which may have implications for the pathogenicity of these ocular isolates.…”
Section: Discussionmentioning
confidence: 73%
“…The type of O-antigen may also confer complement resistance (27). These strains have previously been shown to have different O-antigens (5), so this may be an additional mechanism determining complement resistance. The complement-resistant strains produced far more endotoxin than the complement-sensitive isolates and this was correlated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations